2021
DOI: 10.3389/fmicb.2021.700016
|View full text |Cite
|
Sign up to set email alerts
|

Highly Specific and Sensitive Detection of Yersinia pestis by Portable Cas12a-UPTLFA Platform

Abstract: The recent discovery of collateral cleavage activity of class-II clustered regularly interspaced short palindromic repeats–CRISPR-associated protein (CRISPR-Cas) makes CRISPR-based diagnosis a potential high-accuracy nucleic acid detection method. Colloidal gold-based lateral flow immunochromatographic assay (LFA), which has been combined with CRISPR/Cas-based nucleic detection, usually associates with drawbacks of relative high background and the subjectivity in naked-eye read-out of the results. Here, we dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…Not only the fluorescence quenching reporter ssDNA probe is used to report the detection result, but some systems use other detection methods, such as Cas12a-UPTLFA, combined with LFA technology and up-converting phosphor nanoparticle (UCP) label-coupled detection methods [ 35 ]. The method used a FAM-biotin probe (UPT will be conjugated to biotin), labeled ssDNA as the reporter, and the results were obtained by scanning using a UPT biosensor.…”
Section: Crispr/cas12 Systemsmentioning
confidence: 99%
“…Not only the fluorescence quenching reporter ssDNA probe is used to report the detection result, but some systems use other detection methods, such as Cas12a-UPTLFA, combined with LFA technology and up-converting phosphor nanoparticle (UCP) label-coupled detection methods [ 35 ]. The method used a FAM-biotin probe (UPT will be conjugated to biotin), labeled ssDNA as the reporter, and the results were obtained by scanning using a UPT biosensor.…”
Section: Crispr/cas12 Systemsmentioning
confidence: 99%
“…The results showed that the activated Cas12a can more effectively cleave poly A than poly T, thus G-quadruplex with A bases in the space between G-rich sequences can serve as a more effective reporter than that with T as space bases. It is reported that Cas12a preferred to cut the ploy-C reporter, followed by the poly-A and poly-T reporters sequentially . The number of A bases in the space of G-rich sequence also affected the efficiency of Cas12a trans-cleavage, the values of Δ A of 3 and 6 A bases were 0.38 and 0.52, respectively (Figure B).…”
Section: Resultsmentioning
confidence: 91%
“…Supported by automated microfluidic mixing, an approach for Ebola virus detection was established using Cas13a and achieved an LoD of 20 pfu/ ml (5.45 × 10 7 copies/ml) of purified Ebola RNA within 5 min (Qin et al, 2019). Cas12a-based biosensing was also developed for the detection of a variety of pathogenic microorganisms, such as Listeria monocytogenes , Cryptosporidium parvum (Yu et al, 2021), Salmonella (Ma et al, 2021), Helicobacter pylori (Qiu et al, 2021), Yersinia pestis (You et al, 2021), E. coli, and Staphylococcus aureus (Bonini et al, 2021). Coupling with a reversible valve-assisted chip, sample preparation, Cas12a reactions, and LAMP was integrated and controlled precisely to perform the detection of V. parahaemolyticus, achieving an LoD of 30 copies/reaction within 50 min (Wu et al, 2021b).…”
Section: Sars-cov-2mentioning
confidence: 99%